Genitourinary Tuberculosis: A Comprehensive Review of a Neglected Manifestation in Low-Endemic Countries - Guglielmo Mantica; Francesca Ambrosini; Niccolò Riccardi; Enrico Vecchio; Lorenzo Rigatti; Aldo Franco De Rose; André Van der Merwe; Carlo Terrone; Riccardo Bartoletti; Gernot Bonkat (MDPI AG, 2021)
Genitourinary tuberculosis (GUTB) represents a disease often underestimated by urological specialists, particularly in settings such as the European one, where the pathology is less frequent. Similar to other uncommon diseases at these latitudes, GUTB is a neglected clinical problem. In this light, the aim of this review is to give a comprehensive overview of GUTB in order to provide a useful tool for urologists who seldomly manage this disease. A non-systematic review of genitourinary tuberculosis was performed on relevant articles published from January 1990 to July 2021 using PubMed, Scopus, and the Cochrane Central Register of Controlled Trials. GUTB represents up to a quarter of extrapulmonary tuberculosis (EPTB) cases. Diagnostic, therapeutic and surgical work-up have been deeply reviewed and summarized. The mass migration of refugees to Europe as well as the ease of international travel is gradually leading to an upsurge in urological diseases such as GUTB, which were previously only rarely encountered in some European countries. The poor TB knowledge of European urologists should be improved through medical education courses, webinars or telematic means.